Indigenous communities as custodians in natural forest resource management an evaluation of Dumagat/Remontado tribe as potential forest resource managers in upper Marikina River basin protected landscape - Moussavi, Sarah M. (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
As an sustainable conservation of forests, forest resource management involving indigenous people is required. Indigenous people have developed strong ties to their lands as a result of living there for generations and they were able to manage and retain their traditions despite western colonization. For indigenous people, forests are their habitat. It is not only a resource of their economic needs but it forms a part of their cultural distinctiveness. For forest dwellers, forest has aesthetic and spiritual values. However, indigenous people are considered as invisible in decision making by mainstream planners and policy makers of the protected areas where their ancestral lands are located or in regions where they established their the community. This research stresses the important role of indigenous people in managing and conserving the forest. It considers different facts of the complex relationship of indigenous people and their lands. This relationship is studied in this research according to their forest resource evaluation, landscape resources evaluation, cultural resources evaluation, and human resources evaluation. Further, to gain greater understanding of this relationship the resulting landscape character and their belief system were also documented and evaluated. Among the five villages which the evaluations were conducted, Village 5 has reached the highest score in resource management and therefore capable to be the potential model for natural resource management of Upper Marikina River Basin Protected Landscape. Their concept of sustainability is embodied in their livelihood practices. Rich environmental knowledge which includes the utilization of forest from flora and fauna, use of non-timber products (NTFP) like medicinal plants, organic fertilizers and their belief system made them the potential model.
Thesis (Master of Tropical Landscape Architecture)--University of the Philippines Diliman